2015
DOI: 10.4314/sajas.v45i4.1
|View full text |Cite
|
Sign up to set email alerts
|

Variability in ejaculation rate and libido of boars during reproductive exploitation

Abstract: The main objective of the study was to evaluate variability in the ejaculation rate and libido of boars under various genetic and non-genetic influences. A total of 7171 semen samples were collected from Swedish Landrace, Large White and Duroc boars reared under commercial production conditions. Time spent in preparing or collecting, constituted the period from the entry of boars into the room for collecting semen to onset of ejaculation. Ejaculation rate was defined as the volume of sperm extracted (mL) per u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
(11 reference statements)
2
6
0
Order By: Relevance
“…In this study, more Pietrain than Duroc boars showed increased oxytocin concentrations at T0. The weaker libido of Duroc boars compared with those of others breeds [44,45], as well as the lower total number of sperm and percentage of live sperm in the ejaculates compared with those of Pietrain boars [46], could explain the lower or non-existent increase in salivary oxytocin concentrations at ejaculation time. Furthermore, the age of boars is another influencing factor, as younger boars showed the highest salivary oxytocin concentrations during the ejaculate collection, while the older boars did not show changes between times.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, more Pietrain than Duroc boars showed increased oxytocin concentrations at T0. The weaker libido of Duroc boars compared with those of others breeds [44,45], as well as the lower total number of sperm and percentage of live sperm in the ejaculates compared with those of Pietrain boars [46], could explain the lower or non-existent increase in salivary oxytocin concentrations at ejaculation time. Furthermore, the age of boars is another influencing factor, as younger boars showed the highest salivary oxytocin concentrations during the ejaculate collection, while the older boars did not show changes between times.…”
Section: Discussionmentioning
confidence: 99%
“…It was assumed that longer duration of ejaculation and shorter preparatory time are indicators of a good libido (Savić and Petrović, 2015a). Preparing to collect is a non-productive period (NP) within the total manipulative time, which is calculated from when a boar enters the room with the dummy sow until the end of ejaculation.…”
Section: Libidomentioning
confidence: 99%
“…The use of assisted reproductive techniques in goat breeding provides additional advantages for cryopreservation and artificial insemination [1] . In some cases, certain animals constantly have a high libido and good semen quality for evaluation, freezing or insemination, while others are reluctant for collection and have low quality ejaculates with decreased volume and concentration or other inadequate spermatological characteristics [2][3][4] . During the  İletişim (Correspondence)  +90 312 3170315/4409  ergakcay@gmail.com last decades, specific hormones (oxytocin, prostaglandins, testosterone and GnRH) were introduced to increase the sperm output, quality of male-related reproductive deficiencies and to regulate the breeding activity [5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%